THE PHARMACIST'S ROLE IN MEDICATION AND BREASTFEEDING COUNSELLING - Urška Lučev; Marjeta Rak Namestnik (The Society for Children with Metabolic Disorders, 2022)
The role of the pharmacist in the community is expand-ing, even more, nowadays since the accessibility of doctors is significantly limited. Personal gynaecologists, general practitioners, visiting nurses and pharmacists in the pharmacy play an important role in breastfeeding counselling. It is important that pharmacists are also professionally well-grounded in counselling on problems with breastfeeding and taking prescribed and non-prescription medicines, nutritional supplements and other products during breast-feeding. Thus, nursing mothers receive consistent advice and information from all health professionals who may be involved in breastfeeding assistance. In the postpartum period, more than 50% of women require drug treatment, but because of the fear of taking medication and inadequate information from health professionals during breastfeeding, nursing mothers either do not take medication (regularly) or even stop breastfeeding prematurely. The right information will help the nursing mother weigh the benefits of treatment for her and the risk to the nursing baby. With proper consideration, the mother will find it easier and will more likely continue breastfeeding.